2014
DOI: 10.3389/fbioe.2014.00028
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the IPP Precursor Supply for the Production of Lycopene, Decaprenoxanthin and Astaxanthin by Corynebacterium glutamicum

Abstract: The biotechnologically relevant bacterium Corynebacterium glutamicum, currently used for the million ton-scale production of amino acids for the food and feed industries, is pigmented due to synthesis of the rare cyclic C50 carotenoid decaprenoxanthin and its glucosides. The precursors of carotenoid biosynthesis, isopenthenyl pyrophosphate (IPP) and its isomer dimethylallyl pyrophosphate, are synthesized in this organism via the methylerythritol phosphate (MEP) or non-mevalonate pathway. Terminal pathway engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 85 publications
(118 reference statements)
0
75
0
Order By: Relevance
“…In the newly constructed (ϩ)-valencene producer strain VLC4, the CnVS-encoding gene was expressed after its adaptation to the codon usage of C. glutamicum. In strain VLC6, the genes coding for IspA and CnVS were combined on a single vector, allowing the introduction of a second IPTG-inducible vector for overexpression of the genes encoding the 1-deoxy-D-xylulose 5-phosphate synthase (dxs) and isopentenyl pyrophosphate isomerase (idi) to enhance the supply of the precursors isopentenyl pyrophosphate (IPP) and dimethylallyl pyrophosphate (DMAPP) (18), and consequently, of FPP. Since CnVS gene expression perturbed growth, we presumed that the optimization and timing of CnVS expression would be one key aspect to elevate (ϩ)-valencene production (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the newly constructed (ϩ)-valencene producer strain VLC4, the CnVS-encoding gene was expressed after its adaptation to the codon usage of C. glutamicum. In strain VLC6, the genes coding for IspA and CnVS were combined on a single vector, allowing the introduction of a second IPTG-inducible vector for overexpression of the genes encoding the 1-deoxy-D-xylulose 5-phosphate synthase (dxs) and isopentenyl pyrophosphate isomerase (idi) to enhance the supply of the precursors isopentenyl pyrophosphate (IPP) and dimethylallyl pyrophosphate (DMAPP) (18), and consequently, of FPP. Since CnVS gene expression perturbed growth, we presumed that the optimization and timing of CnVS expression would be one key aspect to elevate (ϩ)-valencene production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…orynebacterium glutamicum represents one of the most important biotechnological platform organisms and massively contributes to the industrial production of amino acids (1)(2)(3)(4)(5), but it has also been engineered, for instance, for the production of lower alcohols (6)(7)(8)(9), organic acids (10-13), diamines (14,15), and carotenoids (16)(17)(18). However, currently applied expression setups show only moderate performance regarding both precise control and expression homogeneity.…”
mentioning
confidence: 99%
“…It is often observed that too high levels of a transmembrane protein such as a transport protein results in growth perturbation [53,54]. In addition, expression levels of several genes of a pathway may need to be tuned to avoid accumulation of potentially inhibitory intermediates as demonstrated for C. glutamicum engineered for decaprenoxanthin overproduction [23]. It is not known if the recombinant C. glutamicum strain WT(pHexA)(pVWEX1-exuT) would be able to grow with sugar acids related to the aldohexuronates Dgalacturonate and D-glucuronate since ExuT is specific for aldohexuronate uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Other strains include C. glutamicum ORN1 [14], C. glutamicum DM1933 [37], and C. glutamicum ΔcrtYEB [23] that are derived from the wild-type strain ( Table 1). The hexuronic acid utilization and transporter genes originated from E. coli MG1655, whereas the strain E. coli DH5α [38] was used for plasmid construction.…”
Section: Microorganisms Plasmids and Cultivation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation